The Effect of Psychological Suzhi on Suicide Ideation in Chinese Adolescents: The Mediating Role of Family Support and Friend Support - Zhu, Zhengguang; Tang, Wenchuan; Liu, Guangzeng; Zhang, Dajun (Frontiers in Psychology, 2021)
In this study, we examined family support and friend support as potential mediators between psychological suzhi and suicide ideation in a sample of 1369 Chinese adolescents (48.1% men, 15.52 ± 1.76 years). The results showed that family support and friend support were found to adequately mediate the relationship between psychological suzhi and suicide ideation. In addition, the effect of psychological suzhi on adolescents’ suicide ideation was stronger for family support than friend support. These findings demonstrated the key roles of psychological suzhi, family support and friend support in reducing adolescents’ suicide ideation. It enlightens us that we are supposed to improve adolescents’ psychological suzhi and perceived social support (including family support and friend support) through many ways in order to better play its protective role in the future.